Efficacy and safety of levetiracetam as adjunctive therapy for refractory focal epilepsy - Maria Luiza Giraldes de MANREZA; Tatiane Amaral PAN; Eduardo Quinalha CARBONE; Antonio Carlos Amedeo VATTIMO; Renata HERRERA; Douglas Costa MORAIS; Rita Antonelli CARDOSO; Glenda Corrêa Borges de LACERDA; Katia LIN; Frederico Nakane NAKANO; Pedro André KOWACS; André Luis Fernandes PALMINI; et al. (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Epilepsy affects about 50 million people worldwide and around 30% of these patients have refractory epilepsy, with potential consequences regarding quality of life, morbidity and premature mortality. Objective: The aim of treatment with antiseizure medications (ASMs) is to allow patients to remain without seizures, with good tolerability. Levetiracetam is a broad-spectrum ASM with a unique mechanism of action that differs it from other ASMs. It has been shown to be effective and safe for treating adults and children with epilepsy. Methods: This was a phase III, multicenter, randomized, double-blind, placebo-controlled trial to evaluate the efficacy and safety of levetiracetam in children and adults (4-65 years) as an adjuvant treatment for focal-onset seizures. It was conducted among 114 patients undergoing treatment with up to three ASMs. The primary efficacy analysis was based on the proportion of patients who achieved a reduction of ≥ 50% in the mean number of focal seizures per week, over a 16-week treatment period. The patients were randomized to receive placebo or levetiracetam, titrated every two weeks from 20 mg/kg/day or 1,000 mg/day up to 60 mg/kg/day or 3,000 mg/day. Results: Levetiracetam was significantly superior to placebo (p = 0.0031); 38.7% of the participants in the levetiracetam group and 14.3% in the control group shows reductions in focal seizures. Levetiracetam was seen to have a favorable safety profile and an adverse event rate similar to that of placebo. Conclusion: Corroborating the results in the literature, levetiracetam was shown to be effective and safe for children and adults with refractory focal-onset epilepsy.